Avian influenza virus in pregnancy. (17th May 2016) - Liu, Shelan; Sha, Jianping; Yu, Zhao; Hu, Yan; Chan, Ta‐Chien; Wang, Xiaoxiao; Pan, Hao; Cheng, Wei; Mao, Shenghua; Zhang, Run Ju; Chen, Enfu
Summary: The unprecedented epizootic of avian influenza viruses, such as H5N1, H5N6, H7N1 and H10N8, has continued to cause disease in humans in recent years. In 2013, another novel influenza A (H7N9) virus emerged in China, and 30% of those patients died. Pregnant women are particularly susceptible to avian influenza and are more likely to develop severe complications and to die, especially when infection occurs in the middle and late trimesters. Viremia is believed to occur infrequently, and thus vertical transmission induced by avian influenza appears to be rare. However, avian influenza increases the risk of adverse pregnancy outcomes, including spontaneous abortion, preterm birth and fatal distress. This review summarises 39 cases of pregnant women and their fetuses from different countries dating back to 1997, including 11, 15 and 13 infections with H7N9, H5N1 and the 2009 pandemic influenza (H1N1), respectively. We analysed the epidemic features, following the geographical, population and pregnancy trimester distributions; underlying diseases; exposure history; medical timelines; human‐to‐human transmission; pathogenicity and vertical transmission; antivirus treatments; maternal severity and mortality and pregnancy outcome. The common experiences reported in different countries and areas suggest that early identification and treatment are imperative. In the future, vigilant virologic and epidemiologic surveillance systems should be developed to monitor avian influenza viruses during pregnancy. Furthermore, extensive study on the immune mechanisms should be conducted, as this will guide safe, rational immunomodulatory treatment among this high‐risk population. Most importantly, we should develop a universal avian influenza virus vaccine to prevent outbreaks of the different subtypes. Copyright © 2016 John Wiley & Sons, Ltd.